The Impact of Customer Experience toward Customer Satisfaction and Loyalty of Ciputra World Surabaya - Chandra, Silvana (iBuss Management, 2014)
Ciputra World Surabaya is facing a tense competition, especially with the  upcoming new  shopping malls. Author believes that customer  satisfaction and  loyalty is the  ultimate solutions  to maintain the visitors traffic, which can be achieved  by encouraging customer experience. The research succeeds  to gather 142 respondents using simple random sampling method. Thus, by applying the Path Analysis with Regression, it  is able to prove that  customer  experience has significant impact toward customer satisfaction  of Ciputra World Surabaya. Then, customer satisfaction  has significant impact toward customer loyalty of Ciputra World Surabaya.  Author also tested  customer satisfaction as mediating variable, however, the result  shows that customer experience has no significant impact toward customer loyalty, mediated by customer satisfaction of Ciputra World Surabaya.  Keywords: Customer Experience,Customer Satisfaction, Customer Loyalty, Ciputra World Surabaya